Bankruptcy as a Corporate Restructuring Mechanism and Its Implications for Corporate Governance and Stakeholder Protection - Hendro Widodo; Subianta Mandala (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Bankruptcy can no longer be understood solely as a mechanism for liquidating assets to meet debtor obligations, but has evolved into a restructuring instrument that directly impacts corporate governance and stakeholder protection. This study aims to analyze how bankruptcy functions as a corporate restructuring mechanism, how this process influences the redistribution of power in corporate governance, and the extent to which the bankruptcy legal system provides balanced protection for various stakeholders. The research method used is normative legal research with a statutory, conceptual, and limited comparative approach. The analysis is conducted on the provisions of Law Number 37 of 2004 concerning Bankruptcy and PKPU (Investment Suspension) and regulations related to corporate governance, combined with theoretical studies on fiduciary duty, stakeholder theory, and the corporate rescue paradigm. The results illustrate that bankruptcy functions as a governance restructuring mechanism that transfers control from the board of directors to the curator and creditor forum, thereby creating a redistribution of power within the company. The dominant creditor primacy orientation has the potential to create an imbalance in protection for non-creditor stakeholders, including workers and other economically impacted parties. These conditions indicate the need for normative reconstruction, including redefining fiduciary obligations during the insolvency phase, strengthening stakeholder protection, and harmonizing corporate governance principles with the insolvency law regime. This research is expected to contribute academically to the development of a bankruptcy model that is not solely focused on debt resolution but also considers aspects of business sustainability and substantive justice in modern corporate governance.